Factors Associated With Facial Nerve Paresis Following Gamma Knife for Vestibular Schwannoma. Issue 1 (January 2020) - Lerner, David K.; Lee, Daniel; Naples, James G.; Brant, Jason A.; Bigelow, Douglas; Alonso-Basanta, Michelle; Ruckenstein, Michael J.
Abstract : Objective: Evaluate the incidence of and potential contributory factors to facial nerve paresis and other cranial neuropathies (CN) following stereotactic radiosurgery with Gamma Knife (GK) for primary treatment of vestibular schwannoma (VS). Study Design: Retrospective chart review. Setting: Tertiary referral center. Patients: Charts were reviewed for all adult patients receiving primary GK treatment for unilateral VS between 2005 and 2013. Patients with NF2 or previous surgery were excluded from analysis. Intervention: GK radiosurgery. Main Outcome Measures: The incidence of new-onset facial nerve paresis after primary GK treatment of VS was evaluated. Secondary endpoints included other cranial neuropathies. Results: One hundred thirty-three patients with VS received primary GK therapy. Posttreatment CN developed in 33 patients (24.8%). Twelve patients (9.0%) experienced trigeminal paresthesia, 11 (8.3%) developed sudden sensorineural hearing loss (SSNHL) requiring steroids, and seven (5.3%) demonstrated facial paresis. The mean maximum cochlear dose was 15.49 Gy in patients with facial paresis compared with 12.42 Gy in subjects without facial paresis ( p = 0.032). Subjects with facial paresis were more likely to have a lateral tumor without fundal fluid on magnetic resonance imaging (MRI) (71%) compared with subjects without facial paresis (43%). Conclusions: In the treatment of VS with primary GK, maximum cochlear dose was significantly associated with facial paresis. Laterally extending tumors without fundal fluid on MRI experienced higher rates of facial paresis. These factors should be considered during GK treatment planning for VS.